Antibodies to autoantigen targets in myasthenia and their value in clinical practice - S. I. Dedaev (Нервно-мышечные болезни, 2015)
Myasthenia gravis is a classic autoimmune disease, which clinical manifestations in the form of weakness and abnormal muscle fatigue, due to the damaging effect of polyclonal antibodies to different structures of the neuromuscular synapse and muscles. The study of autoimmune substrate with myasthenia is routine in many clinics dealing with the problems of neuromuscular pathology, and the identification of high concentration of serum antibodies to a number of antigenic structures is the gold standard in diagnosis.Determination of serum antibodies to various autoimmune targets is an important tool in clinical practice. The majority of patients shows the high concentration of antibodies to AchR that gives the opportunity to use it as an important diagnostic criterion. The specificity of changes in the concentration of AchR-antibodies due to pathogenetic treatment allows to objectify the suppression of autoimmune aggression and evaluate the reliability of remission. However, the absence of AchR-antibodies when there are clear clinical and electromyography signs of myasthenia gravis suggests an autoimmune attack against a number of other targets, the most studied of which is the MuSK. On the contrary, patients with myasthenia gravis associated with thymoma, almost always have a higher level of AchR-antibodies. The presence of thymoma is accompanied by the generation of antibodies to titin and RyR, which is also observed in persons with late-onset myasthenia without thymoma. High concentration of antibodies to these structures can be interpreted as a reliable sign of thymoma in patients younger than 60 years.